Cerebrovascular β‐amyloid deposition and associated microhemorrhages in a Tg2576 Alzheimer mouse model are reduced with a DHA‐enriched diet. Issue 9 (5th April 2018) - Hur, Justine; Mateo, Véronique; Amalric, Nicolas; Babiak, Mégane; Béréziat, Gilbert; Kanony-Truc, Claire; Clerc, Thierry; Blaise, Régis; Limon, Isabelle
ABSTRACT: Cerebral amyloid angiopathy (CAA) is a major contributor to Alzheimeťs disease (AD) pathogenesis. Like AD, CAA is often accompanied by marked inflammation, aggravating associated vasculopathies. No evidence‐based prevention or treatment strategies are available. Here, we evaluate the possible beneficial effect of a diet enriched with docosahexaenoic acid (DHA), which is known to attenuate inflammation in CAA. Tg2576 mice, a transgenic model of AD/CAA, were fed a DHA‐enriched diet starting at 2 mo of age and ending at 10, 14, or 18 mo of age. β‐Amyloid (Aβ)‐peptide deposition and bleeding were visualized by immunohistochemistry or histochemistry on coronal sections of the brain. DHA, arachidonic acid, and eicosanoid levels were measured by liquid chromatography/mass spectrometry or GC‐MS. DHA‐enriched diet throughout aging limits the accumulation of vascular Aβ peptide deposits as well as the likelihood of microhemorrhages. There is a strong correlation between systemic 12‐ hydroxyeicosatetraenoic acid (HETE) levels and the size of the area affected by both vascular amyloid deposits and hemorrhages. The lowest levels of 12‐HETE, a lipid‐derived proinflammatory product of 12‐lipoxygenase (LOX), were found in DHA‐fed mice. In vitro experiments performed on amyloid vascular smooth muscle cells showed that a 12‐LOX inhibitor almost completely blocked the Aβ1, 40 peptide‐induced apoptosis of these cells. This study yet again highlights the important role of inflammation in CAA pathogenesis and identifies potential new targets for preventive care.—Hur, J., Mateo, V., Amalric, N., Babiak, M., Béréziat, G., Kanony‐Truc, C., Clerc, T., Blaise, R., Limon, I. Cerebrovascular β‐amyloid deposition and associated microhemorrhages in a Tg2576 Alzheimer mouse model are reduced with a DHA‐enriched diet. FASEB J. 32, 4972–4983 (2018). www.fasebj.org